Incidence and risk factors for parastomal bulging in patients with ileostomy or colostomy: a register‐based study using data from the Danish Stoma Database Capital Region. (2nd April 2018) - Andersen, R. M.; Klausen, T. W.; Danielsen, A. K.; Vinther, A.; Gögenur, I.; Thomsen, T.
Abstract: Aim: The aim was to investigate the incidence and risk factors for parastomal bulging, a clinically important complication, in patients with an ileostomy or colostomy. Method: The Danish Stoma Database Capital Region prospectively collects data on patients with a stoma up to a year after surgery. Stoma care nurses clinically assessed the main outcome, parastomal bulging. We linked data from the Stoma Database to data from the Danish Anaesthesia Database. Cumulative incidence of parastomal bulging over the first year was calculated with death and stoma reversal as competing risks. Risk factors were investigated using an exploratory approach. Results: In a study population of 5019, the cumulative incidence (with competing risks) of parastomal bulging was 36.2% at 400 days after surgery. Age, colostomy, male gender, alcohol consumption and laparoscopy were associated with an increased risk of parastomal bulging. Compared with cancer, inflammatory bowel disease was associated with a lower risk of parastomal bulging, and diverticulitis was associated with a higher risk. Peristomal mesh and stomas placed through a separate incision were associated with a reduction in risk. There was neither increased nor decreased risk of parastomal bulging for body mass index, American Society of Anesthesiologists score, smoking status, emergency surgery and preoperative stoma site marking. Conclusion: Parastomal bulging is a common complication affecting one in three patients within 1 year of surgery. Along with previous findings, there is now considerable evidence for age and colostomy as being risk factors for parastomal bulging.